NANOTHERANOSTICS IN CARDIOVASCULAR DISEASES: A NOVEL TOOL - NIZAM, IMRANKHAN; AASAITHAMBI, KALAISELVI; SRINIVASAN, ASHA; CHIDAMBARAM, SARVANA BABU; KRISHNAMURTHY, PRAVEEN THAGGIKUPPE; MADHUNAPANTULA, SUBBA RAO V.; THIMMULAPPA, RAJESH; KUPPUSAMY, GOWTHAMARAJAN (International Journal of Applied Pharmaceutics, 2023)
The leading cause of mortality worldwide is cardiovascular disease (CVD). Myocardial infarction, ischemic heart disease, ischemic injury, damaged arteries, thrombosis, and atherosclerosis are among the heart and blood vessel issues referred to as CVD. The most prevalent cause of CVD is atherosclerosis, an inflammatory disease of the arterial blood wall. Because of the complexity of CVD, pathophysiology, diagnosis, and therapy remain vital issues. The inadequacies of current treatment and diagnostic methods have given rise to theranostic nanomaterials. "Theranostic nanomaterials" describes a chemical with dual uses, including therapeutic and diagnostic applications. Theranostic nanoparticle imaging contrast can be advantageous for computed tomography (C. T.), positron emission tomography (P. E. T.), and magnetic resonance imaging (M. R. I.). Additionally, they can cure CVD by employing medication delivery by nanoparticles or photothermal ablation. This study reviews the prevalence of the most recent developments in theranostic nanomaterials for identifying and treating CVD following the order in which diseases advance. Theranostics techniques for CVD detection include M. R. I., CT, near-infrared spectroscopy (NIR), and fluorescence. There have also been discussions of other theranostic nanoparticle-based CVD therapeutic methods.